ESTRATEGIA DE IMPLEMENTACIÓN DE TECNOLOGÍAS DE LA INDUSTRIA 4.0 EN LOS PROCESOS DE TRANSFORMACIÓN OPERATIVA PARA EL SECTOR DE PEQUEÑAS Y MEDIANAS EMPRESAS (PYME) DEL CANTÓN QUEVEDO - Pincay Yagual, Héctor Stalin (2023)
This study presented a strategy for the implementation of Industry 4.0 technologies in the operational transformation processes for the small and medium-sized enterprises (SMEs) sector of the Quevedo canton. A mixed research approach was used, including a literature review and interviews with representatives of local SMEs. The main Industry 4.0 technologies were identified and a methodology for its implementation in SMEs was developed. The results showed that the implementation of Industry 4.0 technologies can significantly improve the efficiency and productivity of SMEs. In addition, the challenges and opportunities of implementing these technologies in the local context were discussed and recommendations for their successful adoption were offered.